Epistemology of Thomas S. Kuhn Shifting Paradigm and Its Relevance to Islamic Science - Putri, Endrika Widdia; Yuwana, Lingga; Afif, Muh. Bahrul (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2020)
This article aims to explain the epistemology of Thomas S. Kuhn's concept of Shifting Paradigm (1922-1996), a postmodernist with its philosophical, physical, and historical expertise, and the relevance of his thinking in Islamic science. The research is a qualitative study using the epistemological point of view to analyze. Kuhns view on the Shifting Paradigm is analyzed based on the important points in the epistemology: the source and substance of knowledge; the instrument of knowledge; how to acquire knowledge; the theory of truth; and Â the validation of the truth of knowledge. The study finds that,Â first, the source and substance of science is the history of science.Â Second, the instrument of knowledge is the paradigm of science.Â Third, knowledge is acquired from the shifting process from the pre paradigm, normal science, anomalies, crises, to a new paradigm.Â Fourth, normal science is the theory of the truth.Â Fifth, the anomaly becomes the validation of the truth. Kuhns thinking of the Shifting Paradigm is relevant to Islamic science because it can be used as a method to explain the transformation of Islamic science. This paper is vital in discussing the relevance of Kuhns thinking to Islamic science. Despite many significant numbers of text on Kuhn's thinking, researchers have not found a text that especially discusses on the epistemology of the Kuhns conception of Shifting Paradigme and point out its relevance to the transformation of Islamic science.